Roles of Indonesia Magnifecence of Zakat in Managing Zakat, Infak and Sadaqah - Asrida, Asrida; Iska, Syukri; Putriana, Vima Tista (International Journal of Multidisciplinary Research of Higher Education, 2023)
Indonesia as a country with a majority Muslim population and at the same time being a country with the largest Muslim population in the world, should ideally have a good zakat management system. In fact, Indonesia only has regulations regarding the management of zakat. The purpose of this study was to find out and understand the implementation of the principles of accountability and transparency in ZIS management by BAZNAS of Tanah Datar Regency. The type of research used is qualitative research, by adopting case study research. Data collection techniques used are through observation, interviews and documentation. This research is analyzed using the concept developed by Miles and Huberman. The researcher collected the necessary data, then reduced the data by focusing on the researcher's views on the implementation of accountability and transparency implemented by BAZNAS of Tanah Datar Regency. From research conducted in the field it can be concluded that BAZNAS of Tanah Datar Regency has implemented the principle of accountability in managing ZIS funds in accordance with the concept developed byIndonesia Magnifence of Zakat both in the decision-making process and in the policy socialization process. Furthermore, for the principle of transparency carried out by BAZNAS, Tanah Datar Regency has not fully implemented the principle of transparency. Of the five indicators of the principle of transparency, there are two principles of transparency that have not been fully implemented by BAZNAS of Tanah Datar Regency, namely the publication of reports on financial position through the mass media and auditing both sharia and finance.